Captain marvel (2014), volume 1 ebook Higher, further, faster, more - special. - DeConnick, Kelly Sue (Captain Marvel (2014),, 2014)
Collects Captain Marvel (2016) #1-5. Oh Captain, my Captain! Carol Danvers soars higher than ever with her greatest mission yet — leading Earth's first line of defense, the all-new Alpha Flight space program! And some alums of the old-school Flight are along for the ride: Puck, Aurora and Sasquatch! It's a bold new frontier for Captain Marvel, but can she handle being a diplomat first and a soldier second? She'll face negotiations with alien delegates, passive-aggressive power struggles with Flight Commander Abigail Brand, an insatiable itch to be out on the front lines and the mystery of a ghost ship bearing the Star of Hala — the very symbol she wears on her chest! Plus: Carol's powers are on the fritz, and all evidence says Alpha Flight has a traitor in its midst. You think your job is tough? Try Captain Marvel's!